Interaction of modulated REB with plasma, formed at its transit through high-density neutral gases - Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Sotnikov, G.V.; Uskov, V.V. (Вопросы атомной науки и техники, 2003)
The theoretical and experimental results of investigations of the relativistic electron beam interactions with plasma, created during its penetration into neutral gas of large pressure, are presented. It is shown that by using of deeply modulated beam it is possible to avoid the depressive influence of dissipation and longitudinal nonuniform plasma density on the beam-plasma interaction efficiency.